O saber ribeirinho como vetor do trabalho pedagógico: uma experiência junto a moradores da comunidade do rio Pirocaba - AMARAL, Luiz Cleibson Ferreira (2022)
The present work discusses the knowledge of the rural-riverside community of Pirocaba, taking the logic of thinking, acting and doing that, in a way, spreads in the ways of organizing the productive life of the residents, in order to problematize their valorization and meaning to school. The central idea was to map knowledge through the voices and records of adults and children, aiming to problematize the rural school in its pedagogical and curricular action, in the sense of a meaningful teaching and aligned with the reality of the subject and riverside context. As a foundation, we base ourselves on the assumptions of authors who discuss the topic, and more especially, on Brandão (2002); when it comes to a community logic of building and circulating knowledge through the mediation of culture and the rural world. Methodologically, the qualitative approach study involved the use of procedures/instruments such as observation, photographic records, interviews with residents and workshops with some children. As a result, we can reaffirm the existence of the knowledge of the riverside community of Pirocaba aligned with the subsistence of life, the integration with nature and the production/transmission/circularity of knowledge by them in the daily life of the community. These knowledge and processes indicate ways of acting, doing and thinking of a people in its peculiarity and culture. These indications point to a school that establishes a connection between formal and informal education, providing opportunities for student-educators; a curriculum-life, culture-education, the (re)construction of teaching with other possibilities, in which the school is a plural and living space, and a teaching that, students and educators, collectively make them think, reaffirm, understand that we are subjects of culture and of the Amazon.